1983
DOI: 10.1161/01.hyp.5.2_pt_2.i198
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm for identification of primary genetic causes of hypertension in rats.

Abstract: A paradigm is developed for identifying the genes (and the biochemical-physiological traits for which the genes code) that cause differences in blood pressure in inbred strains of rats. A biochemical-physiological trait which meets the following four criteria is one which can reasonably be accepted as causing genetic differences in blood pressure: 1) a difference in a biochemical or physiological trait between two strains must be demonstrated; 2) the trait must be shown to follow Mendelian inheritance; 3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 25 publications
0
41
1
Order By: Relevance
“…The presence of the Atp1a1 gene within a QTL where GH alleles are associated with increased blood pressure 12,15 (Figure 2) made it almost mandatory to determine whether the GH rat had the putative A1079T transversion reported by Herrera et al 7,18,25 If the GH rat could be shown to have the transversion, most of the criteria for determining whether this gene is causally involved in hypertension in the GH rat would have been fulfilled. 8 Surprisingly, our results show that neither the GH nor the SS/Jr strain have this transversion.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The presence of the Atp1a1 gene within a QTL where GH alleles are associated with increased blood pressure 12,15 (Figure 2) made it almost mandatory to determine whether the GH rat had the putative A1079T transversion reported by Herrera et al 7,18,25 If the GH rat could be shown to have the transversion, most of the criteria for determining whether this gene is causally involved in hypertension in the GH rat would have been fulfilled. 8 Surprisingly, our results show that neither the GH nor the SS/Jr strain have this transversion.…”
Section: Discussioncontrasting
confidence: 56%
“…2 The reported discovery of an 1079A3 T point mutation in the Atp1a1 allele of the SS/Jr strain 7 presented the possibility of bringing together genetic and physiological findings to explain a component of hypertension in SS/Jr and to fulfill most of the criteria for establishing a gene/causality effect. 8 This mutation would result in a Q276L substitution in the ATPase protein ( Figure 1). Such a substitution was posited to alter the membrane confirmation of Na ϩ ,K ϩ -ATPase, resulting in a change in the Na ϩ -K ϩ pumping ratio and a concordant increase in reabsorption of Na ϩ in the kidney.…”
mentioning
confidence: 99%
“…Using a method of continuous backcrossing of sons to the maternal strain allows the replacement of the autosomal background and the X chromosome. 13 Each generation of backcrossing reduces the paternal autosomal component by 50% (Table 1). By generation F 6 , the new backcross substrains have over 99% of the maternal autosomal genes with the paternal Y chromosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has to be kept in mind, however, that the existence of a genetic difference between inbred strains selected for the presence or absence of a particular trait may be the result of either genetic selection for this trait or chance fixation by genetic drift, as indicated above. To distinguish between these two possibilities, a number of criteria have to be met, 14 including demonstration of a Mendelian pattern of inheritance of the marker, the presence of a logical relation between the gene or gene product investigated and cardiovascular regulation, and the continued association of genotype and phenotype in a segregating population. Structural differences of candidate genes between hypertensive and normotensive subjects can be determined using various methods, including direct sequencing or analysis of restriction fragment length polymorphisms (RFLPs).…”
Section: Candidate Genes For Hypertension In Spontaneously Hypertensimentioning
confidence: 99%